2018
DOI: 10.1155/2018/9671919
|View full text |Cite
|
Sign up to set email alerts
|

Tributyrin Supplementation Protects Immune Responses and Vasculature and Reduces Oxidative Stress in the Proximal Colon of Mice Exposed to Chronic-Binge Ethanol Feeding

Abstract: Excessive ethanol consumption causes adverse effects and contributes to organ dysfunction. Ethanol metabolism triggers oxidative stress, altered immune function, and gut dysbiosis. The gut microbiome is known to contribute to the maintenance of intestinal homeostasis, and disturbances are associated with pathology. A consequence of gut dysbiosis is also alterations in its metabolic and fermentation byproducts. The gut microbiota ferments undigested dietary polysaccharides to yield short-chain fatty acids, pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 57 publications
2
24
0
Order By: Relevance
“…Thus, ethanol-induced gut dysbiosis and subsequent depleted butyrate generation and SCFA transporter expression could compromise the hosts' ability to counteract the harmful effects of LPS on LSEC and hepatocytes. Previously, we found that mice supplemented with butyrate (tributyrin) during chronic-binge ethanol exposure exhibited protection of vascular and endothelial barrier protein expression in the proximal colon [16]. Thus, here we confirmed with an in vitro model the direct beneficial effects of butyrate on endothelial barrier integrity disrupted by ethanol and/or LPS.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, ethanol-induced gut dysbiosis and subsequent depleted butyrate generation and SCFA transporter expression could compromise the hosts' ability to counteract the harmful effects of LPS on LSEC and hepatocytes. Previously, we found that mice supplemented with butyrate (tributyrin) during chronic-binge ethanol exposure exhibited protection of vascular and endothelial barrier protein expression in the proximal colon [16]. Thus, here we confirmed with an in vitro model the direct beneficial effects of butyrate on endothelial barrier integrity disrupted by ethanol and/or LPS.…”
Section: Discussionsupporting
confidence: 88%
“…The assay was performed according to the protocol previously described [14,16] Liver sections and HUVEC monolayers underwent immunostaining for proteins expressed by vascular and endothelial cells (vWF, CD31, Type IV Collagen, E-Cadherin, VE-Cadherin, Claudin-5, and β-catenin), macrophages (F4/80), and for the receptor for advanced glycation end-products (RAGE) in the liver. Specific immunofluorescent positive staining was compared to sections incubated with phosphate-buffered saline (PBS) as a negative control; in these studies no positive staining was seen with PBS incubation.…”
Section: Immunofluescent Stainingmentioning
confidence: 99%
“…Several studies reported that tributyrin reduced intestinal oxidative stress in the ethanol-challenged colitis [41] and colon of dextran sodium sulphate-challenged mice [42]. However, there was little evidence about the antioxidant effect of tributyrin in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, butyrate can downregulate NADPH oxidase in endothelial cells and consequently decrease the oxidative stress in atherosclerotic lesion sites (31). Oxidative stress in the proximal colon of mice induced by chronic-binge ethanol feeding can also be inhibited by NaBu (32). The present study identified that NaBu suppresses HG-induced oxidative stress, inhibits the level of LDH and elevates the level of SOD in NRK-52E cells.…”
Section: Discussionmentioning
confidence: 99%